Rescue from galactose-induced death of Leigh Syndrome patient cells by pyruvate and NAD+. Issue 11 (November 2018) - Iannetti, Eligio; Smeitink, Jan; Willems, Peter; Beyrath, Julien; Koopman, Werner
Abstract Cell models of mitochondrial complex I (CI) deficiency display activation of glycolysis to compensate for the loss in mitochondrial ATP production. This adaptation can mask other relevant deficiency-induced aberrations in cell physiology. Here we investigated the viability, mitochondrial morphofunction, ROS levels and ATP homeostasis of primary skin fibroblasts from Leigh Syndrome (LS) patients with isolated CI deficiency. These cell lines harbored mutations in nuclear DNA (nDNA)-encoded CI genes (NDUFS7, NDUFS8, NDUFV1 ) and, to prevent glycolysis upregulation, were cultured in a pyruvate-free medium in which glucose was replaced by galactose. Following optimization of the cell culture protocol, LS fibroblasts died in the galactose medium, whereas control cells did not. LS cell death was dose-dependently inhibited by pyruvate, malate, oxaloacetate, α-ketoglutarate, aspartate, and exogenous NAD+ (eNAD), but not by lactate, succinate, α-ketobutyrate, and uridine. Pyruvate and eNAD increased the cellular NAD+ content in galactose-treated LS cells to a different extent and co-incubation studies revealed that pyruvate-induced rescue was not primarily mediated by NAD+ . Functionally, in LS cells glucose-by-galactose replacement increased mitochondrial fragmentation and mass, depolarized the mitochondrial membrane potential (Δψ), increased H2 DCFDA-oxidizing ROS levels, increased mitochondrial ATP generation, and reduced the total cellular ATP content. These aberrations were differentially rescued by pyruvate and eNAD, supporting the conclusion that these compounds rescue galactose-induced LS cell death via different mechanisms. These findings establish a cell-based strategy for intervention testing and enhance our understanding of CI deficiency pathophysiology.